Formulation of Medicinal Plants for Respiratory Disorders: Integrating Ayurveda and Tribal Knowledge with Modern Evidence - Purnima Baghel,; Dheeraj Ahirwar,; Bharti Ahirwar, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Respiratory disorders represent a growing global health burden, with increasing demand for safe and effective alternatives to conventional treatments. This study investigates clinically validated herbal formulations from Ayurvedic and tribal traditions of Chhattisgarh, India, focusing on their therapeutic potential for respiratory conditions. Through systematic analysis of ethnopharmacological data and clinical studies, we highlight key medicinal plants - Ocimum sanctum (Tulsi), Justicia adhatoda (Vasaka), Piper longum (Pippali), and Glycyrrhiza glabra (Yashtimadhu) - demonstrating significant clinical efficacy in managing asthma, chronic bronchitis, and COPD. Clinical findings reveal Tulsi's bronchodilatory effects (78% improvement in asthma symptoms in controlled trials) and Vasaka's mucolytic action (82% reduction in sputum viscosity). Pippali shows promise in reducing inflammation markers (IL-6, TNF-α) by 65% in COPD patients, while Yashtimadhu exhibits potent antiviral activity against respiratory pathogens. The study documents standardized formulations from traditional practice, including Vasaka Kwath (decoction) showing 72% efficacy in acute bronchitis cases, and Pippali Churna (powder) reducing cough frequency by 68% in clinical observations. These findings are supported by phytochemical analysis identifying bioactive compounds (vasicine, piperine, ocimene) with demonstrated mechanisms of action. The research emphasizes the need for: (1) larger randomized controlled trials to establish dosage protocols, (2) quality control measures for raw herbs, and (3) integration of evidence-based traditional formulations into pulmonary rehabilitation programs. This work provides a scientific foundation for incorporating clinically validated herbal therapeutics into mainstream respiratory care while preserving traditional knowledge systems.